The case for stronger scrutiny of the deductibility of crypto losses - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2024)
My paper, The Case for Stronger Scrutiny of the Deductibility of Crypto Losses, which was recently published by The Journal of Tax Administration, discusses the issue of crypto losses and risks to the tax base. It submits that tax authorities and national legislatures should step up their scrutiny of the deductibility of crypto losses and proposes some ways in which this can be done in practice.